Predicting a Low Latency in Different States of Emergency Events using Web Resources - Geetha, V; Rajalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
Low latency is basic for intuitive networked applications. Be that as it may, while we know how proportional frameworks to in-wrinkle limit, decreasing latency particularly the tail of the latency dispersion can be a great deal more troublesome. We contend that the utilization of repetition with regards to the wide-territory Internet is a viable approach to change over a little measure of additional limit into diminished latency. By starting excess operations crosswise over differing assets and utilizing the primary outcome which finishes, repetition enhances a framework's latency even under extraordinary conditions. We show that repetition can fundamentally diminish latency for little yet basic undertakings, and contend that it is a successful broadly useful methodology even on gadgets like phones where data transfer capacity is generally obliged.